Optical coherence tomography in progressive cone dystrophy - Zahlava, Jiri; Lestak, Jan; Karel, Ivan (Biomedical papers, 2014)
Aim: The aim of the study was to analyse different clinical pictures in patients with progressive cone dystrophy (PCD), to compare these with the results of optical coherence tomography (OCT) and to evaluate the benefits of this method for diagnosis.Methods: The group consisted of 16 patients (32 eyes) with PCD. All patients were examined for visual acuity, colour sense and visual field. We performed biomicroscopic examination, photo-documentation, fluorescein angiography, electrophysiological tests and OCT.Results: Using biomicroscopy and fluorescein angiography, we found changes in the retinal pigment epithelium ranging from barely detectable changes up to the typical bull's eye appearance. In all the eyes, OCT established statistically significant reduction in the thickness and structural changes in the neuroretina of the macula. Atrophy was evident especially in the outer nuclear layer, in the photoreceptor inner segment/outer segment junction and in the retinal pigment epithelium. Visual acuity was mainly dependent on the degree to which the continuity of the photoreceptor inner segment/outer segment junction layer was maintained. Eyes with better preserved neuroretinal structure in the fovea centralis had generally less reduced thickness of the retina and a better visual acuity.Conclusion: OCT specifies the quantitative and qualitative changes in the macula and may contribute significantly to the diagnosis of the progressive cone dystrophy, particularly in the early stages of the disease which is difficult to diagnose.
Keywords: progressive cone dystrophy; optical coherence tomography; photoreceptor inner segment/outer segment junction; outer nuclear layer